An Edge Based Technique for Spatially Varying Defocus Blur Estimation of Image using Gradient Magnitudes - Simulation & Result - Ahmed Naqvi, Syed Faraz; Niwaria, Kamal; Chourasia, Bharti (International Journal of Computer Sciences and Engineering, 2019)
The article presents a new edge based technique for spatially varying defocus blur estimation with the use of a single image based on reblurred gradient magnitudes. Objects that do not lie at the focal length of a digital camera generate defocused regions in the captured image. Also inherent dynamic features of the nature gives rise to blur in captured image. Whenever there is relative motion between the image to be captured and the imaging system, the image captured at that movement is also suffered by blur. A locally adaptive scheme for obtaining the reblur scales, a connected edge filter for regularizing sparse map, and usingfast guided filter for blur map propagation is recommonded and simulated on Matlab. Results are compared and find to be performing better in comparison with the older adopted methods.